PENGARUH PERSPESI KEMUDAHAN, MANFAAT, RISIKO DAN KEPERCAYAAN TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI (Studi Pada Pelaku UMKM Kota Bandung) - Apriwandi, Apriwandi; Christine, Debbie; Wijaya, Aida; Kartadjumena, Eriana; Sherlita, Erly; Fathonah, Andina Nur (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2023)
This study aimed to determine the interest of small and medium enterprises (SMEs) in using accounting information systems. The interests of SMEs were measured by using the effectiveness of implementing accounting information systems. In addition, behavioral variables were used to bridge the relationship between the perceptions of SMEs on the ease of use, benefits, risks, and trust in the effectiveness of the information system used. The survey method involving a questionnaire was used in this study. The results showed that behavior determines the effectiveness of applying accounting information systems to SMEs. This study also found that it is essential to pay attention to the benefits of the financial accounting system created by the SME company in bringing out a positive attitude from users of accounting information systems.